Understanding public engagement in animal welfare in South Korea: a theory of planned behavior approach - Joo, Seola; Chun, Myung-Sun; Park, Hyomin (Frontiers in Veterinary Science, 2025)
IntroductionHuman-animal relationships have changed significantly in recent decades, becoming increasingly diverse and ethically complex, thereby prompting increased societal concern for animal welfare. This study investigates public perceptions of animal welfare levels and related policies in South Korea, as well as the psychological and contextual determinants of pro-animal behavior as animal welfare engagement, employing the Theory of Planned Behavior (TPB) as its theoretical framework.MethodsA nationally representative online survey was conducted with 2,000 South Korean adults. Measures included attitudes toward animals, subjective norms, internal and external efficacy, behavioral intentions, and self-reported pro-animal behaviors. Structural equation modeling (SEM) was employed to test hypothesized relationships among TPB constructs and behavioral outcomes.ResultsThe findings indicate strong public demand for appropriate and effective political action on animal welfare issues. SEM results show that both pro-animal attitudes and internal efficacy significantly predict behavioral intentions, whereas subjective norms and external efficacy do not exhibit significant effects. Internal efficacy demonstrates both direct and indirect positive influences on pro-animal behavior. In contrast, external efficacy shows no statistically significant direct impact.DiscussionPublic concern for animal welfare in South Korea is increasing, and internal efficacy and pro-animal attitudes play crucial roles in promoting behavioral engagement in animal welfare. Although external efficacy and subjective norms show limited influence, this does not imply that legislative efforts lack value. Rather, institutional support may enhance pro-animal behavior indirectly by strengthening individual confidence, underlining a potential mediating role of internal efficacy between external efficacy and behavioral outcomes. Findings emphasize the need for policies and educational initiatives that enhance individual confidence and motivation while complementing broader institutional frameworks. Future research should incorporate policy feedback theory to better understand the interaction between institutional context and public behavior.